Diet comparison suggests limited competition between invasive black rats (Rattus rattus) and sympatric endangered rodents - Taillie, Paul J.; Boone IV, Wesley W.; Wilson-Seelig, Alexandra L.; McCleery, Robert (Pensoft Publishers, 2024)
Black rats ( Rattus rattus ) are one of the most widespread invasive animals and have been implicated in the decline of species representing several wildlife taxa, particularly on islands. However, their impact on more closely related species, i.e. rodents, via competition is less well-understood. Using diet similarity as a metric of competition for food resources, we used stable isotopes to compare diets of two populations of black rats to diets of two endangered populations of rice rats ( Oryzomys palustris natator and Oryzomys palustris sanibeli ) in southern Florida, USA. Specifically, we analysed hair samples from 32 rice rats and 35 black rats for carbon (δ13C) and nitrogen (δ15N) isotopes. In addition, we analysed samples of 129 potential food items to characterise rodent diets using stable isotope mixing models. Despite considerable overlap in isotope-space, we observed differences between rice rats and black rats in the relative composition of plant and animal foods. Specifically, the diets of both populations of rice rats consisted of mostly animal foods, whereas the diets of black rats consisted mostly of plants. In combination with previous work revealing temporal niche partitioning, our results suggest competition between invasive black rats and endangered native rodents may be limited. As such, expensive and logistically complicated efforts to control black rats may have limited success for conserving endangered rodents.